2015
DOI: 10.1007/s10695-015-0135-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phenol on ovarian P450arom gene expression and aromatase activity in vivo and antioxidant metabolism in common carp Cyprinus carpio

Abstract: Ovarian cyp19a mRNA expression and P450 aromatase activity were measured in vivo in common carp Cyprinus carpio exposed to phenol for 96 h. Production of reactive oxygen species (ROS) and parameters of antioxidant defense system in serum ovary and liver of this fish after long-term phenol exposure were also studied. In vivo exposure of fish to sublethal dose of phenol for 96 h caused marked attenuation of ovarian cyp19a1a gene expression and P450 aromatase activity. Production of ROS like hydrogen peroxide and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 60 publications
1
3
0
Order By: Relevance
“…Croaker were treated with NAME, NEM and an AOX systemically in the present study so they likely exerted similar effects on oAROM as we observed with bAROM. This is supported by a report that an oxidizing agent, phenol, drastically increased H 2 O 2 , a potent ROS, and hydroxyl radical (OH•, a highly reactive ROS) and reduced AROM activity and oAROM mRNA levels in carp ovaries (Das et al, 2016). Treatment of mammalian models with NEM and NO-donors, S-nitro-N-acetylpenicillamine (SNAP) and NOC18, decrease AROM activity and estradiol-17β production by ovarian follicle cells (Snyder et al, 1996;Masuda et al, 2001), and AOX treatment restored AROM activity in placental microsomes after oxidant stress (Milczarek et al, 2008).…”
Section: • -supporting
confidence: 57%
“…Croaker were treated with NAME, NEM and an AOX systemically in the present study so they likely exerted similar effects on oAROM as we observed with bAROM. This is supported by a report that an oxidizing agent, phenol, drastically increased H 2 O 2 , a potent ROS, and hydroxyl radical (OH•, a highly reactive ROS) and reduced AROM activity and oAROM mRNA levels in carp ovaries (Das et al, 2016). Treatment of mammalian models with NEM and NO-donors, S-nitro-N-acetylpenicillamine (SNAP) and NOC18, decrease AROM activity and estradiol-17β production by ovarian follicle cells (Snyder et al, 1996;Masuda et al, 2001), and AOX treatment restored AROM activity in placental microsomes after oxidant stress (Milczarek et al, 2008).…”
Section: • -supporting
confidence: 57%
“…It is known that SOD value can be believed to be a more reliable and expressive set of oxidative stress indicators. High SOD activity in the whole body of 28 day starved fry might be a consequence of free radicals derived from oxidation of lipids [54][55][56][57] .…”
Section: Discussionmentioning
confidence: 99%
“…The absence of effect of E2 on aromatase in adult zebrafish brain may be due to the endogenous estrogenic stimulation on aromatase expression/activities is already high because of the positive autoregulatory feedback loop driven by E2 (Callard et al 2001). Das et al, (2016) and synthetic chemicals on brain and ovarian aromatase activity and P450arom gene expression in fish. Thus, it is imperative that modulation of cyp19b expression can alter the rate of estrogen production, disturbing the local and systemic levels of estrogen, and may lead to disruption of estrogenrelated biological process i.e.…”
Section: Resultsmentioning
confidence: 99%